Pike (Esox lucius) stock management in designated brown trout (Salmo trutta) fisheries: Anglers' preferences - John A. Curtis (The Economic and Social Research Institute (ESRI), 2017)
This paper examines anglers' preferences for active stock management of pike populations within designated wild brown trout fisheries in Ireland. While the policy of pike control has a long history, it is not without controversy and conflict. As the objective of pike control is the protection of trout stocks, a superficial view might be that trout anglers favour and pike anglers oppose such management intervention. Pike and trout anglers do not have homogeneous preferences; in fact, a substantial minority of pike anglers also fish for trout and vice versa. The current paper is the first to examine Irish pike and trout anglers' preferences over fishery attributes, including pike stock control methods. Preference data was elicited by means of choice experiments for pike and trout anglers and a latent class site choice model is used to estimate anglers' utility functions. Not surprisingly model results show that pike anglers do not support pike stock control and almost universally would choose fishing sites where there are no pike stock controls, all else equal. We find that the majority of trout anglers, 61%, are negatively disposed towards pike stock control, and all else equal, are more likely to choose fishing sites where pike stocks are not actively managed. A substantial minority of trout anglers (i.e. 39%) could be considered advocates of pike control, with about one-third of these being more extreme in their preferences, with site choice probabilities of such anglers being largely determined by the pike control management option
Keywords: 330